Sports Coaching for Persons with Disabilities at the National Paralympic Committee - Muhammad Hakim Azkaghani; Fajar Ari Widyatmoko; Husnul Hadi (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study aims to investigate the quality of sports coaching for athletes with disabilities offered by NPCI Demak Regency. The research will also examine the factors that may hinder effective sports coaching for athletes with disabilities provided by NPCI Demak Regency. Materials and methods. This study is descriptive research with a qualitative approach. Qualitative methods were used to describe and analyze the sports coaching for people with disabilities through the Indonesian National Paralympic Committee in Demak Regency. The study also focused on identifying the obstacles that arise from sports coaching provided by the Indonesian Regency National Paralympic Committee in Demak. The informants in this research were the chairman of the Demak Regency NPCI, the Demak Regency NPCI coach, and the Demak Regency NPCI athletes. The research locations included the Indonesian National Paralympic Committee in Demak Regency and the sports training site at NPCI Demak Regency. Results. The sports coaching program for athletes with disabilities offered by NPCI Demak Regency involves identifying potential athletes with disabilities, providing specialized training, offering access to sports facilities and infrastructure, and recognizing the achievements of athletes with disabilities. However, challenges such as limited transportation options for people with disabilities and inefficient time management present barriers to the effectiveness of the program. Conclusion. The sports coaching program for athletes with disabilities offered by NPCI Demak Regency is progressing smoothly in line with the established plans. This includes identifying potential athletes with disabilities, tailoring training to specific sports, ensuring access to sports facilities and infrastructure, and recognizing athletes with awards for their accomplishments.